A four-wire reduced bus capacitance UPFC for LV distribution networks with high PV penetrations - Haque, M.; Wolfs, Peter (2014)
© 2014 ACPE. In this paper, we propose a low voltage (LV) distribution level four-wire unified power flow controller (UPFC) for voltage regulation and phase current balancing. This device is shown capable of regulating the positive, negative and zero sequence voltage in LV distribution networks under high PV penetrations. At same time, the device is capable of power factor correction, zero sequence or neutral current compensation and a degree of negative sequence current compensation. Instantaneous reactive power theory shows that DC-bus capacitor power will fluctuate at twice mains frequency during any unbalanced operation of the regulator. Real and instantaneous power balance of UPFC can be maintained by allowing the input shunt converter to draw a small positive and negative sequence current respectively. Instantaneous power balance with negative sequence current makes it possible to reduce the DC bus capacitance which allows long life ceramic or polypropylene capacitors to replace electrolytic capacitors.